2014
DOI: 10.1038/bmt.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stem cell transplant patients with acute respiratory failure requiring mechanical ventilation in the United States

Abstract: SCT indications and procedures are increasing worldwide. We sought to estimate the prevalence of acute respiratory failure (ARF) of any cause in hospitalized SCT patients, and assess the impact of invasive mechanical ventilation (IMV) on outcomes. We hypothesize that duration of IMV in such patients is an independent predictor of higher mortality. We performed a retrospective analysis of the largest all-payer hospitalization data set in the United States, Nationwide In-patient Sample for years [2004][2005][200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…67,70,71 The need for ventilatory support ranges from 28 to 76% in recent studies, 13,16,21,24,25,[27][28][29][30][31][32][33][34][35] and ICU mortality varies from 63 to 85% (Table 3). These results are far worse than the respective 70% and 62% ICU and hospital survival rates reported in a large observational study of unselected ICU patients requiring MV.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…67,70,71 The need for ventilatory support ranges from 28 to 76% in recent studies, 13,16,21,24,25,[27][28][29][30][31][32][33][34][35] and ICU mortality varies from 63 to 85% (Table 3). These results are far worse than the respective 70% and 62% ICU and hospital survival rates reported in a large observational study of unselected ICU patients requiring MV.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…3,9,10 The retrospective design of our study precludes us from drawing a true cause and effect relationship, nevertheless, the associations we found appear to have merits. Our study identified only those patients who had an IHCA and received CPR, it did not identify the population who had IHCA but did not receive CPR due to DNAR status or deemed futile.…”
mentioning
confidence: 82%
“…8,9 It is imperative to identify and evaluate the risk factors associated with IHCA requiring CPR in this cohort so as to inform the patients, surrogates or providers involved in care and to optimize outcomes.…”
mentioning
confidence: 99%
“…In a previous issue of the journal, Allareddy et al 1 report on the prevalence of acute respiratory failure from any cause in hospitalized SCT patients and the associated hospital costs. The authors utilized the Nationwide Inpatient Sample (NIS), which is the largest all-payer inpatient database in the United States, approximating 97% of all hospital discharges annually.…”
mentioning
confidence: 99%
“…Prior to recent advances, respiratory failure requiring mechanical ventilation following SCT had mortality rates between 85-90%. 2 Allareddy et al 1 found an overall mortality rate between 60.6 and 66.5% for SCT patients requiring mechanical ventilation. These numbers, although significantly improved compared with older studies, are still well above the o 30% mortality reported for those requiring mechanical ventilation for respiratory failure in the general population.…”
mentioning
confidence: 99%